Comparative study on bilateral lower extremity joint mechanics and muscle synergy patterns in Axel jumps between elite and amateur single skaters - Yu, Jialiang; Li, Mingda; Chen, Zhiyuan (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundThis study aimed to reveal the differences in lower limb joint kinematic characteristics and muscle synergy patterns during the Axel jump between amateur and elite figure skaters, providing a theoretical basis for scientific training. Research on this topic, especially regarding in-depth analysis of detailed lower limb joint kinematics and muscle synergy patterns, remains insufficient.MethodsThree-dimensional motion capture systems and surface electromyography (sEMG) were used to synchronously collect kinematic and sEMG data from subjects during the approach, take-off, and flight phases of the Axel jump. OpenSim was used to process data on lower limb joint angle changes. Non-negative matrix factorization (NMF) was employed to analyze muscle synergies, muscle weighting, and activation coefficients.ResultsSignificant differences (P < 0.05) were found in the dynamic changes of multiple left lower limb joint angles between elite and amateur athletes during the approach-to-take-off phase. Specifically, significant differences (P < 0.05) were observed in hip flexion/extension (1%–13%), abduction/adduction (49%–53%), and external/internal rotation (1%–2%) angles at specific intervals of the movement cycle. Similarly, significant differences (P < 0.05) were found in knee flexion/extension (49%–51%), ankle dorsiflexion/plantarflexion (54%), and subtalar joint dorsiflexion/plantarflexion (21%) angles. Muscle synergy analysis revealed six synergies for the amateur group and five for the elite group. In synergy 1, related to the initial phase of the movement, the contribution weight of the left tibialis anterior was significantly higher in elite athletes (F = 15.21, P = 0.0005). In synergy 2, elite athletes activated their primary muscles during the approach-to-take-off transition phase (38%–62%), which was earlier and more concentrated than the activation in amateur athletes during the take-off-to-flight phase (59%–78%).ConclusionThe approach and take-off phases of the Axel jump are crucial for distinguishing between amateur and elite athletes. Elite athletes demonstrate more coordinated and efficient movement strategies and exhibit superior motor performance in the activation timing of key muscles. This suggests that training should focus on enhancing lower limb control capabilities and the early, efficient activation of key muscles during these phases.